A Study of the Financial Accounting Software Used by Small Enterprises in Olsztyn - Kowalewski, Mirosław; Niedzielska, Joanna (Olsztyn Economic Journal, 2015)
The objective of this paper is to assess the financial-accounting software used in small enterprises operating business in the area of Olsztyn in Warmińsko-Mazurskie voivodship. The research material was acquired by means of the questionnaire-based survey targeted at selected small enterprises situated in Olsztyn. Out of 50 questionnaires distributed 18 (36%) were returned. Based on the survey conducted, it was determined that the majority of the enterprises surveyed use standard, generally accessible financial-accounting software. The extensive choice of standard software in the market is the most frequently indicated factor determining the purchase of software of that type. The acquisition of accounting software is decided less frequently on the price, and more on the standard software being known to the employees and the software availability. Small enterprises use both the obligatory registers (functions) and numerous optional registers available in the financial-accounting software they possess.